Microenvironment Influences Odontogenic Mesenchymal Stem Cells Mediated Dental Pulp Regeneration - Huang, Xiaoyao; Li, Zihan; Liu, Anqi; Liu, Xuemei; Guo, Hao; Wu, Meiling; Yang, Xiaoxue; Han, Bing; Xuan, Kun (Frontiers in Physiology, 2021)
Dental pulp as a source of nutrition for the whole tooth is vulnerable to trauma and bacterial invasion, which causes irreversible pulpitis and pulp necrosis. Dental pulp regeneration is a valuable method of restoring the viability of the dental pulp and even the whole tooth. Odontogenic mesenchymal stem cells (MSCs) residing in the dental pulp environment have been widely used in dental pulp regeneration because of their immense potential to regenerate pulp-like tissue. Furthermore, the regenerative abilities of odontogenic MSCs are easily affected by the microenvironment in which they reside. The natural environment of the dental pulp has been proven to be capable of regulating odontogenic MSC homeostasis, proliferation, and differentiation. Therefore, various approaches have been applied to mimic the natural dental pulp environment to optimize the efficacy of pulp regeneration. In addition, odontogenic MSC aggregates/spheroids similar to the natural dental pulp environment have been shown to regenerate well-organized dental pulp both in preclinical and clinical trials. In this review, we summarize recent progress in odontogenic MSC-mediated pulp regeneration and focus on the effect of the microenvironment surrounding odontogenic MSCs in the achievement of dental pulp regeneration.